Ethnomedicinal knowledge of traditional healers on medicinal plants in Sukoharjo District, Central Java, Indonesia - RIRIN NUR FADHILAH; NILAM SARIRAMADHANI KOESDARYANTO; THAARIQ RIAN PRIBADY; REISHA AZZAHRA PUTRI RESTANTA; GILANG DWI NUGROHO; AHMAD YASA; PUGUH SUJARTA; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fadhilah RN, Koesdaryanto NS, Pribady TR, Restanta RAP, Nugroho GD, Yasa A, Sujarta P, Setyawan AD. 2023. Ethnomedicinal knowledge of traditional healers on medicinal plants in Sukoharjo District, Central Java, Indonesia. Biodiversitas 24: 4223-4234. Indonesia is blessed with the world's largest biological diversity, reflected in the tens of thousands of species of plants that occur in Indonesia. This privilege benefits the community by using it in everyday life, including in the health sector. Medicinal plants have various benefits, such as relieving cough, fever, wounds, and other body system problems. Sukoharjo District, Central Java, Indonesia, is known as a center of traditional herbal medicine (Jamu), and the people in this district have used medicinal plants in the traditional medicine practiced by various healers or shamans. However, this local wisdom has not been documented scientifically. This study aims to collect data on ethnomedicinal knowledge of traditional healers in Sukoharjo and relevant information regarding medicinal plants used by them, including the taste of the plant. The method used in this research was a combination of direct observation, field notes, and in-depth interviews with several traditional healers. The study documented that 75 species of medicinal plants belonged to 41 families dominated by the Zingiberaceae family. Most of the plant parts of the medicinal plants used are the leaf, mostly consumed by boiling, resulting in a bitter taste drink. Common diseases to cure with traditional medicinal plants include coughs, fever, flatulence, diarrhea, diabetes, menstrual pain, flu, toothache, and ulcers. The findings of this study highlight that even though modern medicine is available, people still trust traditional healers and utilize medicinal plants, which are important for preserving ethnomedicinal knowledge in a region.